Politics Most Unusual - Cox, Damian. author. aut Link
XIV, 198 p.
Keywords: How has 9/11 and the declaration of the 'global war on terror' changed our conceptions of politics? How has it affected our understanding of democracy, personal freedom and government accountability? In answering these and other questions, the authors engage in a comprehensive and critical analysis of politics in the age of terrorism.